Towards a multimodal repository of expressive movement qualities in dance - Piana, S.; Coletta, P.; Ghisio, S.; Niewiadomski, R.; Mancini, M.; Sagoleo, R.; Volpe, G.; Camurri, A. (Proceedings of the 3rd International Symposium on Movement and Computing, 2016)
In this paper, we present a new multimodal repository for the analysis of expressive movement qualities in dance. First, we discuss guidelines and methodology that we applied to create this repository. Next, the technical setup of recordings and the platform for capturing the synchronized audio-visual, physiological, and motion capture data are presented. The initial content of the repository consists of about 90 minutes of short dance performances movement sequences, and improvisations performed by four dancers, displaying three expressive qualities: Fluidity, Impulsivity, and Rigidity.